Citra Merek dan Iklan terhadap Keputusan Pembelian dengan Celebrity Endorser Memoderasi Iklan - Diffa Okta Astridianty; Suharyanto Suharyanto (Oikonomia: Jurnal Manajemen, 2022)
The purpose of this study was to analyze the effect of brand image and advertising on purchasing decisions with celebrity endorsers moderating advertising. Methodology The population in this study are those who buy products at Bukalapak who live in Jabodetabek. The sample size used in this study was 100 respondents, using a non-probability sampling technique which was chosen by using a purposive judgmental sampling technique. The tools for analysis techniques use IBM SPSS version 26, the MRA (Moderated Regression Analysis) analysis technique was selected, carried out in stages. Findings The results showed that the variable brand image, advertising has a positive effect on purchasing decisions. The moderating variable is celebrity endorser negatively moderating the relationship between advertising and purchasing decisions. In addition, celebrity endorsement has a direct positive influence on purchasing decisions but when it is a moderator it weakens the relationship between advertising and purchase decisions. Suggestions Companies need to be extra careful in the use of celebrity endorsements combined with advertising, because the nature of the two do not support or strengthen each other but reduce and may replace. Further research is needed to determine the combination of these two variables.